2021
DOI: 10.1515/dx-2021-0032
|View full text |Cite
|
Sign up to set email alerts
|

The role of D-dimer in periprosthetic joint infection: a systematic review and meta-analysis

Abstract: Objectives The current literature on diagnosis of periprosthetic joint infection (PJI) provides controversial evidence on the diagnostic accuracy of D-dimer. Therefore, this critical literature search and meta-analysis was aimed to summarize the diagnostic accuracy of D-dimer for diagnosing PJI. Content We searched MEDLINE, Scopus, and Web of Science, for studies on D-dimer for diagnosing PJI, according to the PRISMA flowchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
1
13
0
1
Order By: Relevance
“…Serum D-dimer demonstrated excellent diagnostic value with an AUC of 0.91, far above that of plasma D-dimer (AUC of 0.66). Other authors have further supported this finding[ 80 , 82 - 87 ]. Some studies have reported no difference in baseline D-dimer levels when using either of the two techniques, however, Boisclair et al [ 89 ] reported significant differences in sensitivity and specificity when examining serum vs plasma D-dimer in the diagnosis of disseminated intravascular coagulation, DVT, and myocardial infarction[ 88 , 89 ].…”
Section: Periprosthetic Joint Infectionsupporting
confidence: 62%
See 1 more Smart Citation
“…Serum D-dimer demonstrated excellent diagnostic value with an AUC of 0.91, far above that of plasma D-dimer (AUC of 0.66). Other authors have further supported this finding[ 80 , 82 - 87 ]. Some studies have reported no difference in baseline D-dimer levels when using either of the two techniques, however, Boisclair et al [ 89 ] reported significant differences in sensitivity and specificity when examining serum vs plasma D-dimer in the diagnosis of disseminated intravascular coagulation, DVT, and myocardial infarction[ 88 , 89 ].…”
Section: Periprosthetic Joint Infectionsupporting
confidence: 62%
“…A collection of systematic reviews and meta-analyses were recently published in an effort to eliminate confusion and draw clarity from the literature[ 80 - 87 ]. The overall pooled data displays that D-dimer has good diagnostic accuracy to detect PJI.…”
Section: Periprosthetic Joint Infectionmentioning
confidence: 99%
“…Причины, способствующие увеличению значений D-димера у пациентов с асептической нестабильностью: тромботические расстройства, воспалительные заболевания, послеоперационные состояния, онкозаболевания, инфекции, травмы,кровоизлияния и даже коронавирусная болезнь (COVID-19). D-димер в основном является маркером системного фибринолиза и оборота фибрина, так что на его значения потенциально могут влиять многие факторы: возраст, пол, индекс массы тела, сопутствующие сердечно-сосудистые заболевания, требующие лечения антикоагулянтами [34]. Высокая доля отклонений значений D-димера от нормы в нашем исследовании (41,8%) может быть объяснена отсутствием информации о сопутствующих заболеваниях пациентов, которые могли оказать значительное влияние на значения D-димера.…”
Section: Discussionunclassified
“…Furthermore, serum d ‐dimer measurement was recently proposed as part of the PJI diagnostic workup due to its potential diagnostic accuracy. Recently, three meta‐analyses reported discordant results in evaluating the accuracy of serum d ‐dimer in diagnosing PJI 18–20 . We, therefore, asked: (1) What are the most appropriate thresholds for d ‐dimer and fibrinogen in patients with painful total knee arthroplasty?…”
Section: Introductionmentioning
confidence: 99%